La periferia izquierda de la palabra: prefijos y elementos compositivos - Martín García, Josefa (El Colegio de México, 2020)
This paper examines in detail the differences between combining forms and prefixes. Specifically, it is argued that combining forms function as nouns and therefore can be arguments and combine with suffixes. On the other hand, prefixes show less specific meanings as a consequence of the loss of lexical features, which allows them to become operators and form semantic scales. Since this grammaticalization process occurs in differing degrees, prefixes do not show an homogeneous behaviour.